The Uneven Distribution of Unemployment in the United Kingdom, 1929-36 - Champernowne, D. G. (Review of Economic Studies, 1938)
Journal Article The Uneven Distribution of Unemployment in the United Kingdom, 1929–36 Get access D. G. Champernowne D. G. Champernowne London Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 5, Issue 2, February 1938, Pages 93–106, https://doi.org/10.2307/2967523 Published: 01 February 1938